Landasan Psikologi Kurikulum - Akbar, Meiza Fajar; Firdaus, Ahmad Haikal (DIKLINKO JOURNALS PUBLISHER, 2023)
This research discusses the psychological foundation, which is one of the principles in curriculum development, as it influences human behavior and how they learn. The psychological foundation in curriculum development plays a key role in designing educational curricula. In this context, the psychological foundation of the curriculum includes a deep understanding of students' cognitive, emotional, and social development. Articulating learning objectives that align with the stages of psychological development can enhance educational effectiveness. The research method used is library research, a type of qualitative research involving the collection, analysis, processing, and presentation of books, journals, and texts related to the research theme as reference materials in the form of a literature report. The research findings on the psychological foundation of the curriculum reveal two concepts: 1) the psychological foundation of the curriculum includes Developmental Psychology, Learning Psychology, and Social Psychology. 2) The elements of the curriculum foundation encompass Student Development and Curriculum, Learning Psychology, and Curriculum Development.